(untitled) (Global Journal of Medical Research, 2022)
Getting sick, in general, is an unexpected and frustrating event in people’s lives, providing feelings such as anxiety, fear and anguish. Cicely Saunders classifies the set of physical, emotional, environmental, and social sensations that such an event causes as "Total Pain", which includes both the patient and the companions. In this context, it is essential that the health professional is prepared to welcome the patient and company with a humanized approach, also seeking to solve non-physical pain in the hospital environment. Thus, humanization becomes an indispensable item at all levels of care.